Problemas ligados ao álcool em centros de emergência (PLACE)—People experiencing homelessness with alcohol-related problems in Lisbon's emergency shelters during the COVID-19 pandemic: a description and analysis of a harm reduction intervention - Azevedo, Filipe Oliveira; Neto, Ana; Gama, Ana; Subtil, Ana; Fuertes, Ricardo; Pereira, Claúdia; Tavares, Joana; Medinas, Raquel Luis; Silva, Ana V.; Dias, Sónia (Frontiers in Psychology, 2023)
Introduction: As the first wave of the COVID Pandemic spread, a growing need to improve and monitor the living conditions of Lisbon’s Homeless Population led to the creation of Emergency Shelters. Pandemic difficulties in obtaining alcohol, due to reduced offer as well as diminished economic capacities, could have led to increasing withdrawal syndromes and so a low threshold harm-reduction intervention was initiated in the emergency shelters. This innovative approach consisted in a fixed medication treatment, made available immediately for those with specific conditions, without the need of previous medical evaluation or abstinence of alcohol intake, and later access to medical appointments in addiction specialized centers. The PLACE study (Alcohol Related Problems in Emergency Shelters) is a retrospective mixed-methods observational study that aims to evaluate the harm reduction intervention as well as the experience of the patients, professionals and decision makers involved. This article aims to do a quantitative analysis of those who presented alcohol related problems in Lisbon’s emergency shelters in 2020. Methods: This is a descriptive cross-sectional analysis of those enrolled in the program using the PLACE study database. Results: 69 patients self-reported alcohol related problems, of which 36.2% accepted a pharmacological intervention and 23.2% reached an addictions appointment. This was associated with better housing outcomes. A description of demographic, health, and social characteristics as well as trajectory after leaving the shelter is provided. Discussion: Alcohol related problems disproportionally affect people experiencing homelessness. Non-abstinence focused interventions may reach a broader range of patients and can be useful and well tolerated in treating addiction in this population.